Price and hedonic heterogeneity measures in local housing markets - Dag Einar Sommervoll (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2023)
In this paper, we develop a local housing stock heterogeneity measure. This measure may be used to monitor housing stock heterogeneity over time and in combination with other measures of policy interest. We illustrate the latter by looking at local housing stock heterogeneity, house price variation (measured by local Gini coefficients), and affordability measures.
hdl:11250/3046944
Keywords: R31; R21; C43; 330; Housing market; Heterogeneity; segregation